Evaluating organ dose and radiation risk of routine CT examinations in Johor, Malaysia - M.K.A. Karim,; S. Hashim,; A. Sabarudin,; D.A. Bradley,; N.A. Bahruddin, (Penerbit Universiti Kebangsaan Malaysia, 2016)
In this study, radiation doses from CT scan procedures and its related risks to the patients from five hospitals in Johor State, Malaysia were analyzed. The survey was conducted in a two-month period encompassing data for 460 patients with the number for each hospital being set at 32, 30 and 30 samples for CT brain, CT thorax and CT abdomen, respectively. The results indicated that the CTDIw, DLP and effective dose values ranged from 7.0±1.3 to 67.7±3.4 mGy, 300.2±135.4 to 1174.2±79.9 mGy.cm and 1.5±0.2 to 11.7±6.65 mSv, respectively. The organ doses were calculated using CT EXPO software (Ver. 2.3.1, Germany) and were found to vary within the hospitals and the type of the CT examinations. Effective cancer risks per procedure were calculated by multiplying organ dose with the nominal cancer risk that was adapted from International Commission on Radiological Protection (ICRP) Publication 103. The values ranged from 0 to 1449 cancer cases per one million procedures for these three routine examinations. This present work showed that the CT systems can impart high radiation doses and increase of radiation risk to patients if optimization protocols are ignored.